RANCANG BANGUN TELEPON TESTER VERSI 2.0 - Indra Kumala Sari; Maya Pitaloka; Nonot Harsono (SAINTEKBU, 2008)
The telephone set which is daily used , could get a failure  any time. So it’s introduced a peripheral that could determine which parts of telephone gets malfunction. It is called a telephone tester which checks four parts of telephone circuit, they are ringer circuit, microphone and speaker of  handset, and DTMF ( Dual Tone Multi Frequency ) keypad. In this final project we made  a Telephone Tester Version 2.0 with the same function of telephone tester before ( Version 1.0). The design of this telephone is basically different from first telephone tester with a better performance.In manufacturing the peripheral,  four separated circuits are used to determine the failure of a telephone set. On the circuit of ringer tester, IC 555 is used to generate ring tone with time period is 1s ‘on’ and 2s ‘off’; on the handset’s microphone tester circuit, OP-AMP 741 is used; on circuit of handset’s speaker tester, Wien oscillator ( f = 400 Hz) is used as tone generator; and on the DTMF keypad tester circuit, MT 8870 IC DTMF Receiver and DT-51 microcontroller are used with LCD ( Liquid Crystal Display ).With this peripheral, we could certainly know the malfunction parts of telephone set, so the repairement could be done immediately.Keywords: ring tone, microphone, speaker, DTMF keypad, IC 555, IC 741, MT 8870, microcontroller DT51, oscillator Wien, LCD ( Liquid Crystal Display ).